Dobrodziej – mistrz – profesor. Wincenty Pol w świetle listów doń skierowanych - Nowak-Barcińska, Małgorzata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The author of the article researches how Wincenty Pol was described in the letters he was sent to. The research corpus contained 98 letters addressed to Pol by a variety of senders, compiled by Zbigniew Sudolski in an anthology: Letters from our Land. Wincenty Pol’s Epistolography, 1826-1872. Of particular interest are the statistically significant forms of address: patron, professor, master, prophet, kin. The forms used for addressing Wincenty Pol depict him as e.g.: father of the nation and a prophet; an adored – if not worshipped – and respected professor. These forms confirm Suchodolski’s claim about the vital role of the author of Mohort in “shaping the culture of his times”. At same time, the expressions under analysis are a testimony of the rich language etiquette of the time.